2018
DOI: 10.1111/apha.13049
|View full text |Cite
|
Sign up to set email alerts
|

Atrium‐specific ion channels in the zebrafish—A role of IKACh in atrial repolarization

Abstract: We demonstrate that the acetylcholine-activated inward-rectifying current (I ) current plays a major role in the zebrafish atrium and that the zebrafish could potentially be a cost-effective and reliable model for pharmacological testing of atrium-specific I modulating compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Zebrafish hearts operate over a similar range of heart rates (HRs) and have similar action potential (AP) characteristics to mammalian hearts (Hove-Madsen, Llach et al 1998, Gillis and Tibbits 2002, Milan, Jones et al 2006, Leong, Skinner et al 2010) , Skarsfeldt, Bomholtz et al 2018). However, the zebrafish system is relatively simple and contains all the essentials for functioning while maintaining the flexibility needed to adjust to myriad environmental stressors, such as temperature (6-38 °C) (Spence, Gerlach et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish hearts operate over a similar range of heart rates (HRs) and have similar action potential (AP) characteristics to mammalian hearts (Hove-Madsen, Llach et al 1998, Gillis and Tibbits 2002, Milan, Jones et al 2006, Leong, Skinner et al 2010) , Skarsfeldt, Bomholtz et al 2018). However, the zebrafish system is relatively simple and contains all the essentials for functioning while maintaining the flexibility needed to adjust to myriad environmental stressors, such as temperature (6-38 °C) (Spence, Gerlach et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our robust I KACh signal was concomitant with more clear mature sarcomeric subcellular structure, which was less obvious in other protocols with robust I KACh signal [8]. We highlight I KAch for particular note given the major importance of this current in atrial repolarization and membrane stability and its implication in atrial fibrillation [47; 48] which makes a robust I KACh current likely a necessity for meaningful modeling of atrial fibrillation, drug development, and translational work using hiPSC-derived atrial cardiomyocytes. All these features make cells derived using our new Gremlin 2/RA protocol suitable for the testing of beneficial and harmful effects of drugs on human cardiac atrial muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous assays, limited to the visualization of the hearth rhythm in the transparent embryo (Milan et al, 2003), electrocardiography allowed for a detailed analysis of the cardiac depolarization, repolarization, and conduction, based on quantification of PR, QRS, or QT interval durations (Milan et al, 2006). Several research groups subsequently modified the recording technique in order to improve the feasibility, the signal-to-noise ratio, and the accuracy of the recordings (Liu et al, 2016;Lin et al, 2018;Skarsfeldt et al, 2018;Zhao et al, 2019). These studies demonstrated that, despite the evident anatomical differences between the human and the two chambered zebrafish heart, their electrocardiographic characteristics at baseline were highly comparable.…”
Section: Electrophysiology Of the Zebrafish Basal Electrocardiogram Similar To That Of Humansmentioning
confidence: 99%
“…Genes responsible for the atrium-specific small conductance Ca 2+ -activated K + SK channels, KCa2.1-3 (KCNN1, KCNN2, KCNN3); for the leak channels TASK1 and TASK3 (KCNK3 and KCNK9); and the acetylcholine−activated current, I KACh , (KCNJ3 and KCNJ5) have been reported in adult zebrafish heart. However, direct current recordings have shown that the acetylcholineactivated inwardly rectifying current, I KACh , is functional and significant in the zebrafish atrium, whereas TASK and SK channels are not relevant for the regulation of the atrial AP (Skarsfeldt et al, 2018).…”
Section: Background Channelsmentioning
confidence: 99%